A priori estimates of solutions of linear parabolic problems with coefficients from Sobolev spaces - Romanenko, I. B.; Skrypnik, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider the general initial-boundary-value problem for a linear parabolic equation of arbitrary even order in anisotropic Sobolev spaces. We prove the existence and uniqueness of a solution and establish ana priori estimate for it.